alpha-Sympathomimetic amines and calcium-mediated action potentials in guinea-pig ventricular muscle. - Ledda, F. (Nature Publishing Group, 1980)
1 The ability of amines, having alpha- or alpha- and beta-adrenoceptor stimulating activity, to restore excitability and contractility in heart preparations partially depolarized by potassium, was investigated in guinea-pig ventricular muscle in order to elucidate the mechanism of the positive inotropic effect mediated via alpha-adrenoceptors. 2 In preparations in which fast sodium channels were inactivated by K+-rich medium (22 mM) slow electrical responses as well as contractions were consistently induced by high concentrations of phenylephrine (10(-4) to 3 X 10(-4) M) and synephrine (3 X 10(-4) M). 3 The restorative effective effects of both phenylephrine and synephrine were unaffected by phentolamine (10(-5) M) but were readily abolished by practolol (10(-5) M) or sotalol (10(-5) M). 4 Methoxamine induced a dose-dependent positive inotropic effect in ventricular strips paced at 0.5 Hz in normal Tyrode solution; the maximum increase in contractile tension was obtained with methoxamine 10(-4) M. However, at the same concentration, the amine did not induce slow electrical responses in potassium-depolarized preparations. 5 It is concluded that the induction of slow responses by phenylephrine and synephrine is due to beta-adrenoceptor stimulation, and that the increase in cardiac contractility caused by alpha-adrenoceptor stimulation does not involve an increase in slow inward calcium current.